Safety Strategies of Genetically Engineered T Cells in Cancer Immunotherapy - Ren, Yan-Bei; Sun, Shang-Jun; Han, Shuang-Yin (Current Pharmaceutical Design, 2018)
T-cell therapy using genetically engineered T cells modified with either T cell receptor or chimeric antigen receptor holds great promise for cancer immunotherapy. The concerns about its toxicities still remain despite recent successes in clinical trials. Temporal and spatial control of the engineered therapeutic T cells may improve the safety profile of these treatment regimens. To achieve these goals, numerous approaches have been tested and utilized including the incorporation of a suicide gene, the switch-mediated activation, the combinatorial antigen recognition, etc. This review will summarize the toxicities caused by engineered T cells and novel strategies to overcome them.
Keywords: T-cell therapy